استخدام أكسيد القصدير 2SnO الناقل الشفاف كمو جه للأشعة تحت الحمراء - دويس, دعاء; شعبانة, شيماء (university of eloued جامعة الوادي, 2023)
تم في إطار هذا العمل ترسيب أغشية رقيقة من أكسيد القصدير 2SnO النقية والمطعّمة بالفلور ) 0% , 3% , 6% , 7% , 8% , 9% ( والأنتموان ) 0% , 0.6% , 0.8% , 1% ( بتقنية الرش بالانحلال الكيميائي الحراري على ركائز زجاجية مسخّنة تحت درجة حرارة 480℃ لمدّة 3 دقائق. حيث اظهرت نتائج الدراسة أن لأغشية أكسيد القصدير القدرة على توليد استجابة غير خطية من الدرجة الثالثة وهذا نظرًا لخصائصها الكهربائية )ناقلية عالية( والضوئية الجيّدة إذ يكون تفاعل الأغشية مع الضوء تفاعل غير خطي في مجال الأشعة تحت الحمراء القريبة، حيث أن قرينة الانكسار تكون صفرية أو سالبة وهذا ما يبرّر التصرف البلازمي للمادة. انطلاقًا ممّا سبق نرى أنه بالإمكان استعمال أكسيد القصدير كمصدر ضوئي لتوليد التوافقيات الجديدة.In this study, we employed a chemical dissolution spraying fluorine doped with 2SnOtechnique to deposit thin films of pure (0%, 3%, 6%, 7%, 8%, 9%) and antimony (0%, 0.6%, 0.8%, 1%) on preheated glass substrates at 480℃ for 3 min. the results of our investigation revealed that tin oxide films possess the ability to exhibit a third-order nonlinear response. This behavior can be attributed to their excellent electrical conductivity and optical properties. This films exhibit a nonlinear interaction with light in the near-infrared range, where the refractive index is close to zero or even negative. This phenomenon can be attributed to the plasma-like behavior of the material. Based on the findings mentioned above, tin oxide emerges as a potential source for generating new harmonics.
mémoer master phizeque
Keywords: أكسيد القصدير، الفلور، الانتموان، استجابة غير خطية، قرينة الانكسار، البلازما الانحلال الكيميائي الحراري.; tin oxide, fluorine, antimony, nonlinear response, refractive index, plasma, thermochemical decomposition.